Neuroplasticity in a range of induced effects of transcranial electrical stimulation - Voloshyna, Nataliia P.; Chernenko, Maksym Ye.; Gaponov, Petro K. (Psychiatry, Neurology and Medical Psychology, 2020)
This article presents the results of an analysis of modern scientific data on the induction of neuroplasticity using transcranial electrical stimulation. Three types of effects arising from the use of transcranial electrical stimulation are considered: central, peripheral and mixed. The central effects are analgesia, stabilization of hemodynamics, relief of pain. Peripheral effects include slowing the growth of tumors, modulating the dynamics of the acute phase response during inflammation, accelerating the healing of skin wounds, ulcerative defects of the gastric mucosa, and the focus of necrosis in myocardial infarction. Of the mixed effects are antistress, antipruritic, antitoxic effects. All of the above effects are based on the release of beta-endorphins. Potentiation of the effects of transcranial electrical stimulation is caused by enkephalinase inhibitors, 5-HT precursors, monoamine oxidase and tryptophanpyrrolase inhibitors. The features of the therapeutic effects of transcranial electrical stimulation are highlighted: they have a homeostatic character and are manifested both comprehensively and systemically. The effect on neuroplasticity by transcranial direct current stimulation (tDCS) was examined. tDCS is presented as a modulator of global neural activity. It was shown that tDCS leads to the activation of neurons and astrocytes through neurovascular conjugation, directly affects the cells of the vascular endothelium, and helps increase the speed of blood flow in the capillaries. It was shown that transcranial electrical stimulation has a corrective effect on clinical electrophysiological parameters in patients with neurogenic bladder dysfunction and nocturnal enuresis, has a stimulating effect on glial cells, diversifies the brain neurochemical status, modifies the synaptic microenvironment, regulates various neurotransmitters, and increases BDNF secretion. Studies show that tDCS led to a significant decrease in glutamate and glutamine in the anterior cingulate gyrus, a tendency to decrease glutamate and glutamine in the thalamus, and a tendency to increase GABA in the anterior part of the islet. Thus, transcranial electrical stimulation is a method capable of providing long-term therapeutic effects of stimulation and affect the processes of neuroplasticity.